NILAI IBADAH TERHADAP EFISIENSI BANK UMUM SYARIAH - M. Fahmi Hidayat; Roikhan M. Aziz (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study investigates the efficiency of Islamic banking in Indonesia from 2018 to 2021 through the application of Data Envelopment Analysis (DEA), incorporating Islamic principles. The analysis utilizes secondary financial data from four Islamic banks, sourced from the Financial Services Authority (OJK) and other researchers. The input variables considered include third-party funds allocated for profit-sharing and labor costs, while the output variables consist of revenue derived from the management of public funds and other operational income. The DEA results indicate fluctuating efficiency levels among the Islamic banks, with Bank Syariah Y consistently achieving 100% efficiency, signifying its status as the most efficient institution. The study identifies that revenue from public fund management negatively impacts the growth of Islamic banks, whereas labor costs and other operational income positively influence their development. These findings highlight areas requiring improvement and the factors driving efficiency in the development of Islamic banking in Indonesia.